2017
DOI: 10.1177/1010428317691178
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 functions as a tumor suppressor in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma is one of the leading causes for cancer-related mortality worldwide. SIRT3 may function as either oncogene or tumor suppressor in a panel of cancers; however, the role of SIRT3 in hepatocellular carcinoma remains unclear. In this study, we assayed the expression level of SIRT3 in hepatocellular carcinoma tissues by quantitative reverse transcriptase-polymerase chain reaction and immunohistochemistry. A loss-of-function approach was used to examine the effects of SIRT3 on biological act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…As reported previously, SIRT3 controls the EMT process and metastatic motility of cancer cells through Twist in ovarian carcinoma [55]. In addition, SIRT3 has the capability to suppress cell migration and invasion in HCC and pancreatic ductal adenocarcinoma [50,51]. However, some conflicting reports have shown that the high expression of SIRT3 is interrelated with positive lymph node metastasis in breast cancer and disclosed an association between the levels of SIRT3 and lymph node metastasis [117].…”
Section: Sirtuins and Tumor Metastasismentioning
confidence: 74%
See 1 more Smart Citation
“…As reported previously, SIRT3 controls the EMT process and metastatic motility of cancer cells through Twist in ovarian carcinoma [55]. In addition, SIRT3 has the capability to suppress cell migration and invasion in HCC and pancreatic ductal adenocarcinoma [50,51]. However, some conflicting reports have shown that the high expression of SIRT3 is interrelated with positive lymph node metastasis in breast cancer and disclosed an association between the levels of SIRT3 and lymph node metastasis [117].…”
Section: Sirtuins and Tumor Metastasismentioning
confidence: 74%
“…Apoptosis NSCLC [40] P53 CCA [41] MYC Metastasis HCC [42,43] AKT/GSK3β/β-catenin Axis GC [44] Tumorigenesis BC [45] Slug HCC [39] APC, CDC20 BC [39] APC, CDC20 SIRT3 Viability BLC [46] P53 PC [47] MYC; PI3K/AKT pathway CRC [48] AKT/PTEN NSCLC [49] Bax/Bcl-2, P53 HCC [50] PI3K/AKT pathway PDC [51] Apoptosis NSCLC [49] Bax/Bcl-2, P53 OSCC [52] RIP Leukemia [53] AKT, Bax/Bcl-2 Metastasis CRC [48] AKT/PTEN HCC [50] PI3K/AKT pathway PDC [51] PC [54] FOXO3A, Wnt/β-catenin pathway OC [55] Twist [57] ERK/Drp1 Axis ESCC [58] GDH CRC [59] GC [60] Apoptosis Metastasis NSCLC [57] ERK/Drp1 Axis ESCC [58] GDH CRC [59] E-cadherin GC [60] E-cadherin [72] COX-2, AKT, AMPK CRC [73] PTEN/AKT signaling ACC [74] NF-κB signaling GBM [75] JAK2/STAT3 pathway Apoptosis CRC [73] PTEN/AKT signaling HCC [70] Bax GBM [75] AK2/STAT3 pathway FSA [76] NF-κB signaling HCC [77,78] ERK1/2 pathway CC [76] NF-κB signaling Metastasis HCC [71,79] PKM2 CRC…”
Section: Sirtuins and Viability In Cancersmentioning
confidence: 99%
“…Kong et al showed that SIRT3 is a downstream target gene of PGC-1α in hepatocytes and mediates the suppressive effects of PGC-1α on ROS production [202]. SIRT3 can also inhibit growth and proliferation of the human hepatoma cells HepG2 and induce apoptosis [203] and is a tumor suppressor in the human hepatoma cells Huh7, reducing phosphorylation of PI3K/Akt [204]. Of note, SIRT3 expression is downregulated in human HCC [203,204] and low SIRT3 expression is associated with poor differentiation and unfavorable prognosis [205].…”
Section: Mitochondrial Dysfunction In Nash-associated Hccmentioning
confidence: 99%
“…In the liver, both SIRT3 mRNA and protein levels were found significantly downregulated in tissues from patients with HCC [131][132][133][134] and HCC tumor cell lines [131,134]. Lower levels of SIRT3 were also associated with reduced overall and recurrence-free survival, reduced tumor differentiation, more tumors in advanced stages, higher serum alpha-fetoprotein levels, and multiple tumor numbers [134].…”
Section: Sirt3mentioning
confidence: 99%
“…Lower levels of SIRT3 were also associated with reduced overall and recurrence-free survival, reduced tumor differentiation, more tumors in advanced stages, higher serum alpha-fetoprotein levels, and multiple tumor numbers [134]. In HepG2 cells, SIRT3 overexpression suppressed cell growth, invasion, and apoptosis [131,132], and SIRT3 upregulation induced the expression of MnSOD, p53, BAX, and FAS [132].…”
Section: Sirt3mentioning
confidence: 99%